Pengalaman Kecemasan Akademik dan Sosial Mahasiswa Perantau Pasca Banjir serta Dampaknya Terhadap Kesejahteraan Mental - Arima Arima; Marimbun Marimbun (Journal of Society Counseling, 2026)
This study was conducted due to the limited existing research on the impact of floods on out-of-state students at Indonesian universities, particularly regarding social disruptions, academic disruptions, changes in learning patterns, and post-disaster psychological conditions. The study aims to analyze the experiences of out-of-town students affected by the flood at IAIN Langsa. The method used is a descriptive qualitative approach through in-depth interviews with ten out-of-town students directly affected by the flood in February 2026. Data were analyzed using thematic analysis to identify the main themes of the respondents’ experiences. The results indicate that the flood caused academic issues such as exam postponements, difficulties in accessing academic guidance, and uncertainty regarding graduation. Students also experienced changes in learning patterns due to limited access to learning infrastructure and disrupted communication with family, which triggered social isolation and anxiety. Psychological impacts such as stress, trauma, and excessive anxiety were also identified as long-term effects. This study concludes that more responsive campus policies are needed through continuous psychosocial support, academic flexibility, and improved access to online learning to aid the recovery of students living away from home following a disaster.